1998
DOI: 10.1128/aem.64.10.4084-4088.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effective Recovery of Bacterial DNA and Percent-Guanine-Plus-Cytosine-Based Analysis of Community Structure in the Gastrointestinal Tract of Broiler Chickens

Abstract: A DNA-based, direct method for initial characterization of the total bacterial community in ileum and cecum of the chicken gastrointestinal (GI) tract was developed. The efficiencies of bacterial extraction and lysis were >95 and >99%, respectively, and therefore the DNA recovered should accurately reflect the bacterial communities of the ileal and cecal digesta. Total bacterial DNA samples were fractionated according to their percent G+C content. The profiles reflecting the composition of the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(71 citation statements)
references
References 31 publications
1
70
0
Order By: Relevance
“…Analysis of %G+C base pro¢les might give an indication of di¡erences in bacterial community structure at the community level. Such analyses have been used to demonstrate di¡erences in bacterial communities of aquatic and terrestrial environments [34], of compartments in an activated sludge system [35] and of compartments in the gastrointestinal tract of chickens [36]. In terrestrial environments, the bacterial communities of two pristine forest soils have been shown to di¡er in %G+C base pro¢les [20].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of %G+C base pro¢les might give an indication of di¡erences in bacterial community structure at the community level. Such analyses have been used to demonstrate di¡erences in bacterial communities of aquatic and terrestrial environments [34], of compartments in an activated sludge system [35] and of compartments in the gastrointestinal tract of chickens [36]. In terrestrial environments, the bacterial communities of two pristine forest soils have been shown to di¡er in %G+C base pro¢les [20].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the adherent bacteria sample, a sample of 2 mL was vortexed thoroughly after 6 mL of PW was added. Bacterial cells were recovered from each sample using a differential centrifugation technique modified from Apajalahti, Särkilahti, Mäki, Heikkinen, Nurminen and Holben (1998). In brief, the liquid mixture was centrifugated at 200 g for 15 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Equal amounts of ileal or caecal digesta from the ten birds within each treatment at each sampling were combined for preparation of bacterial samples that were subsequently used for DNA extraction. Bacterial samples from ileal digesta were prepared by a washing procedure as described by Apajalahti et al (1998), whereas caecal digesta was used directly for DNA extraction. Samples for DNA extraction were frozen in liquid nitrogen and stored at )70°C.…”
Section: Chicken Maintenance and Sample Collectionmentioning
confidence: 99%